Multifunctional Spirogyra-hyalina-Mediated Barium Oxide Nanoparticles (BaONPs): Synthesis and Applications - Abdullah; Anees ur Rahman; Shah Faisal; Mervt M. Almostafa; Nancy S. Younis; Galal Yahya (Molecules, 2023)
This research aims to biosynthesize Barium oxide nanoparticles (BaONPs) for biomedical applications, using Spirogyra hyalina as a stabilizing and reducing agent. UV–visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), energy-dispersive X-ray, X-ray diffraction (XRD), and scanning electron microscopy (SEM) were used to physiochemically characterize the barium oxide nanoparticles, while antibacterial, minimum inhibitory concentration, antifungal, free radicle scavenging, and anti-inflammatory assay were performed to assess the therapeutic potential of the synthesized BaONPs. Fourier transform infrared spectroscopy revealed bands at 615 and 692 cm−1 that corresponded to the formation of BaONPs. Scanning electron microscopy revealed the spherical and flower-shaped morphology of BaONPs having an average diameter of 64.01 ± 2.0 nm. Both Gram-positive and Gram-negative bacterial growth was halted by the barium nanoparticles, demonstrating their efficacy up to 19.12 ± 0.31 mm against E. coli, 18.83 ± 0.44 mm against Klebsiella pneumoniae, 17.31 ± 0.59 mm against P. aeruginosa, 16.56 ± 0.37 mm against S. aureus, and 15.75 ± 0.38 mm against S. epidermidis, respectively. The minimum inhibitory concentration was 9.0, 6.3, 5.5, 4.5, and 2.0 µg/mL for S. aureus, Klebsiella pneumoniae, S. epidermidis, P. aeruginosa, and E. coli, respectively. BaONPs were not that effective against fungal strains such as Rhizoctonia solani, Fusarium solani, and Fusarium proliferatum. The BaONPs exhibited potent anti-inflammatory and antioxidant activity through inhibiting cyclooxygenases type 1 (43.12 ± 1.21%) and 2 (41.23 ± 1.56%), and DPPH free radicles up to 43.52 ± 0.29% at 400 µg/mL. In conclusion, the biomolecules derived from Spirogyra hyalina have demonstrated remarkable ability to generate stable nanoparticles, offering promising prospects for their utilization as therapeutic agents and coating materials in various biomedical applications.